2021
DOI: 10.7759/cureus.16424
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Role of Ethylenediaminetetraacetic Acid (EDTA) in the Treatment and Understanding of Psoriasis

Abstract: Psoriasis is a long-term, autoimmune inflammatory condition characterized by red, scaly plaques that can range from a few patches to total skin coverage. Over the past 60 years, and more recently, the metalchelating agent ethylenediaminetetraacetic acid (EDTA) has proven increasingly useful in the treatment and understanding of psoriasis and related conditions. This review will analyze the current role and effectiveness of EDTA in clinical and non-clinical studies designed to improve the diagnosis and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…The clams that would have a greater feeding rate would be able to filter more food from the environment, leading to an increased rate of survivability in their environment. The mechanism of filter feeding mainly depends on the spacing of the gills in the clams [8,[11][12][13][14][15]. The two main sources of food for C. Fluminea in this experiment were algae and E. coli.…”
Section: Discussionmentioning
confidence: 87%
“…The clams that would have a greater feeding rate would be able to filter more food from the environment, leading to an increased rate of survivability in their environment. The mechanism of filter feeding mainly depends on the spacing of the gills in the clams [8,[11][12][13][14][15]. The two main sources of food for C. Fluminea in this experiment were algae and E. coli.…”
Section: Discussionmentioning
confidence: 87%
“…In this investigation, the authors attempt to develop an AI software that can be utilized to diagnose cases where patients have exudative or non-exudative macular degeneration in either their left eye, their right eye, or both eyes. Our investigation builds upon previous studies that have demonstrated how AI software can accurately diagnose macular degeneration within a patient [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 87%
“…Despite all the progress that has been made in the efforts to understand OIH so far, further research is still required in order to develop a more permanent treatment for those who suffer from this condition and are far beyond the threshold for naltrexone co-treatment. Perhaps other medications that break down the production of beta-lipoproteins, such as the metal-chelator ethylenediaminetetraacetic acid (EDTA), could be used in stabilizing and analyzing nociceptive and μ-opioid receptors for more novel treatment options [27]. Additionally, more research should be conducted to determine the side effects of naltrexone so that patients can make a more informed decision before their physician provides them with treatment options.…”
Section: Reviewmentioning
confidence: 99%